Interplay between Singlet and Triplet Excited States in Interface Exciplex OLEDs with Fluorescence, Phosphorescence, and TADF Emitters. (20th November 2022) - Zhou, Zeyang; Chen, Rui; Jin, Pengfei; Hao, Jinjie; Wu, Wubin; Yin, Baipeng; Zhang, Chuang; Yao, Jiannian
Abstract: Interface exciplex represents a promising host material for organic light‐emitting diodes (OLEDs) with barrier‐free charge injection and highly confined recombination region. However, the efficiency of radiative recombination in pristine exciplex is usually low and needs to be improved by doping various emitters. In this study, the interface exciplex OLEDs doped with fluorescence, phosphorescence, and thermally activated delayed fluorescence (TADF) emitters is fabricated to investigate the relationship between their excited‐state properties and electroluminescence efficiencies. A maximum external quantum efficiency of 20% is achieved in interface exciplex OLEDs doped with TADF emitter, which corresponds to nearly 100% exciton utilization and is superior to those of fluorescence and phosphorescence emitters. Furthermore, optical spectroscopy and magneto‐electroluminescence method are used to study the advantages of TADF emitter in interface exciplex host. The large dipole of TADF emitter is beneficial for harvesting energy from the charge‐transfer state at the interface, and its reverse intersystem crossing avoids the accumulation of triplet excitons that leads to triplet‐triplet annihilation in interface exciplex OLEDs. These results demonstrate that the photophysical process needs to be carefully considered in designing high‐performance emitters for exciplex host materials, and it may bring in‐depth understanding on improving exciton utilization and electroluminescence efficiency in interface exciplex OLEDs. Abstract : In this study, the relationship between excited‐state processes and electroluminescence efficiencies in interface exciplex organic light‐emitting diodes (OLEDs), is systematically investigated. Nearly 100% exciton utilization is observed when thermally activated delayed fluorescence (4CzPN) emitter is doped in the active layer of the interface exciplex OLEDs by simultaneously activating the Förster and Dexter energy transfer channels and suppressing the triplet‐triplet annihilation process.